Pengembangan Panduan Bibliokonseling untuk Meningkatkan Self Esteem pada Peserta Didik SMA di Karanganyar - Kevin Setiawan; Agus Tri Susilo; Citra Tectona Suryawati (Jurnal Psikoedukasi dan Konseling)
Abstract: This research and development aim to produce products that meet the relevance criteria, namely the development of bibliocounseling guidelines to increase self-esteem in high school students in Karanganyar. Based on the results of empirical and theoretical studies ready to meet the criteria of consistency, efficiency, and effectiveness. This research uses research and development methods according to Plomp & Nieveen, which are divided into three stages; preliminary research, development phase (prototyping), and assessment phase. Product development is based on preliminary investigation analysis through questionnaires and interviews. This research and development have only reached the second stage, namely the development or prototyping phase, which has been carried out to produce a product, namely guidelines and worksheets for counseling and counseling to increase self-esteem in high school students in Karanganyar. The resulting bibliocounseling guidelines meet the relevance criteria. Relevance criteria were obtained through empirical studies and theoretical studies. The product in this study still needs to meet the criteria for consistency, practicality, and effectiveness to reach the research and development phase of the assessment phase. This manual consists of two books, namely (1) manuals and (2) worksheets. Suggestions for further researchers to be able to proceed to the next stage, namely the assessment phase, and examine the acceptability of this product in the broader scope of the school.